The Limits of Polycentrism at the City-regional Scale: The case of Luxembourg - Antoine Decoville (Politecnico di Torino, 2014)
Over the last fifteen years, promoters of the European spatial planning policy have presented polycentrism as the most promising strategy for answering the challenge of a more even spatial development. However, there is still no empirical evidence proving that this conceptual tool is adaptable to all scales. In this paper, we propose two different approaches of urban hierarchy with regards to its capacity to structure spatial development at a city-regional scale: the Grand Duchy of Luxembourg. The first one depicts a classical urban hierarchy based on the location of urban amenities. The second one, which takes into account the accessibility to these amenities, shows the polycentric model in a more nuanced manner. Our results underline the differences between these two models and call for caution with respect to the adoption of the polycentric model at this spatial scale, since it could potentially lead to an increase in urban sprawl.